Perancangan Aplikasi Pengenalan Sistem Tata Surya untuk Kelas 6 SD Augmented Reality Berbasis Android - Pandu Dewanata; Thoyyibah T. (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The solar system consists of the Sun as the central star and various other objects within its gravitational influence. Augmented Reality (AR)-based learning is increasingly developing as an innovative educational approach that is more engaging and interactive. With AR technology on the Android operating system, students can understand solar system concepts more visually and dynamically. AR allows users to interact with virtual objects in the real world by combining elements of virtual reality (VR) and the physical environment. In solar system learning, this technology helps students explore three-dimensional (3D) objects more intuitively.Android, as a Linux-based operating system commonly used on portable devices, enables the widespread adoption of AR in education. With a high number of Android users, AR technology has the potential to be an effective solution for enhancing students' understanding of the solar system and other celestial bodies.